PENENTUAN ZONA PROSPEK PANASPENENTUAN ZONA PROSPEK PANAS BUMI ‘‘AR‘‘ MENGGUNAKAN METODE DENSITAS SESAR DAN REKAHAN - DETERMINATION OF GEOTHERMAL PROSPECT ZONE ‘‘AR‘‘ USING FAULT AND FRACTURE DENSITY (FFD) METHOD - Pramudito, Andaru; Hendrasto, Fajar; Setyorini, Dyah Ayu; Hariyadi, Nurkholis (JURNAL PENELITIAN DAN KARYA ILMIAH LEMBAGA PENELITIAN UNIVERSITAS TRISAKTI, 2025)
Geothermal exploration requires efficient and reliable methods for assessment of surface conditions. One such method is the Fault and Fracture Density (FFD) method, which involves the analysis of faults and fractures intensity within a geothermal area. The FFD method is widely used in geothermal exploration as it provides important information about the structural properties of a geothermal field. This method allows for the delineation of fault and fracture zones, which are crucial components of a geothermal system. These fault and fracture zones correspond to the reservoir of geothermal systems, as they provide pathways for fluid flow and heat transfer. The FFD method is particularly useful in the early-stage exploration of geothermal resources as it provides an estimation of geothermal prospect area distribution. The method calculates the intensity of faults and fractures within a given area. The FFD contour delineation as a geothermal prospect zone is in the contour range of 2-4 km/km2, which is located in the southeast and center of the "AR" geothermal field. This area has a highest lineament density intensity. The Way Wejak Fault, Watuwater Fault and Atalojo Fault are found on an FFD contour of 2-4 km/km2, this confirms that these three faults act as permeable zones where geothermal fluids come out from below to the surface which is related to the presence of geothermal manifestations along the faults which shows that these three faults are directly connected to the reservoir zone.